2018
DOI: 10.1021/acsnano.8b07421
|View full text |Cite
|
Sign up to set email alerts
|

Swimming to Stability: Structural and Dynamical Control via Active Doping

Abstract: External fields can decidedly alter the free energy landscape of soft materials and can be exploited as a powerful tool for the assembly of targeted nanostructures and colloidal materials. Here, we use computer simulations to demonstrate that nonequilibrium internal fields or forces -forces that are generated by driven components within a system -in the form of active particles can precisely modulate the dynamical free energy landscape of a model soft material, a colloidal gel. Embedding a small fraction of ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 80 publications
2
17
0
Order By: Relevance
“…Here, Pe 1,2 is the global Péclet number and it represents the relative significance of advective transport in region 1 compared to diffusive transport in region 2. By comparing (A1)-(A6) and (A7)-(A14), we observe an interesting difference between passive-like ABPs (U > 0 and Pe → 0) and passive Brownian particles (PBPs; U = 0 and so Pe = 0), which show the identical diffusion-dominated dynamics [31,32]. The number density changes only when there exists variation of swim speed.…”
Section: Appendix A: Analytical and Numerical Solutions For An Infinimentioning
confidence: 87%
“…Here, Pe 1,2 is the global Péclet number and it represents the relative significance of advective transport in region 1 compared to diffusive transport in region 2. By comparing (A1)-(A6) and (A7)-(A14), we observe an interesting difference between passive-like ABPs (U > 0 and Pe → 0) and passive Brownian particles (PBPs; U = 0 and so Pe = 0), which show the identical diffusion-dominated dynamics [31,32]. The number density changes only when there exists variation of swim speed.…”
Section: Appendix A: Analytical and Numerical Solutions For An Infinimentioning
confidence: 87%
“…Mixtures provide an additional degree of control for performing specific functions. For example, doping a monodisperse Brownian system with ac-tive particles can help anneal crystals and rapidly relax jammed states [26,27]. Many active living systems interact not only with passive Brownian particles and obstacles but also with other active species, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Opportunities in colloidal assembly were further stressed by recent numerical works that considered mixtures of active, autonomously-driven particles, in passive phases. They showed that the presence of active particles can favor the annealing of a passive polycrystal by melting its grain boundaries 2527 or act as an internal field to control the structural and dynamical properties of a colloidal gel 28 . Notwithstanding, experimental realizations of mixtures of active particles in a passive phase are scarce and have not demonstrated control of the passive phase.…”
Section: Introductionmentioning
confidence: 99%